Chlorogenic acid prevents paraquat-induced apoptosis via Sirt1-mediated regulation of redox and mitochondrial function. (3rd June 2019) - Kong, Deqin; Ding, Yaqi; Liu, Jiangzheng; Liu, Rui; Zhang, Jiaxin; Zhou, Qingbiao; Long, Zi; Peng, Jie; Li, Lin; Bai, Hua; Hai, Chunxu
Abstract: Paraquat (PQ) is a widely used agro-chemical in agriculture and highly toxic to humans. Although the mechanism of PQ poisoning is not clear, it has been well documented that reactive oxygen species (ROS) generation and apoptosis play pivotal roles. Alternatively, chlorogenic acid (CA) is a biologically active dietary polyphenol, playing several therapeutic roles. However, it is not known whether CA has protective effect on PQ-induced apoptosis. Here, we investigated the effect of CA in preventing PQ-induced apoptosis and explored the underlying mechanisms. A549 cells were pretreated with 100 µM CA for 24 h and then exposed to 160 µM PQ for 24 h. We found that CA was effective in preventing PQ-induced apoptotic features, including the release of cytochrome c from the mitochondria to cytoplasm, the cleavages of caspase 3 and caspase 9, and the increases in levels of Bcl-2-associated X protein (Bax) and intracellular calcium ions. CA alleviated ROS production and prevented the reduction of antioxidant capacity in cells exposed to PQ by increasing NF-E2-related factor 2 (Nrf2), superoxide dismutase 2 (SOD2) and glutathione levels. In addition, CA also attenuated PQ-induced alterations of mitochondrial structure and function (such as the decreases in membrane potential and adenosine triphosphate level), and the impaired autophagic flux was improved by CA. Down-regulation of sirtuin 1 (Sirt1) by short hairpin RNA reversed the protective effects of CA. Thus, CA may be viewed as a potential drug to treat PQ-induced lung epithelial cell apoptosis and other disorders with similar pathologic mechanisms.